Type A aortic dissection during in pregnancy: Confront without aversion or delay. Issue 6 (25th March 2022) - Idhrees, Mohammed; Jubouri, Matti; Bashir, Mohamad; Velayudhan, Bashi V.
Abstract: Type A aortic dissection (TAAD) is a life‐threatening clinical emergency requiring timely surgical intervention. Concomitant with pregnancy at any stage, it adds an additional level of complexity which mandates careful planning for the management strategy that will yield the optimal outcomes. It is life‐threatening pathology to both the mother and fetus, with mortality rates of up to 30% and 50% reported, respectively. Safe imaging modalities that do not expose the fetus to radiation and contrast are recommended to reach an accurate diagnosis. In addition, meticulous multidisciplinary team planning is pivotal to ensure optimal outcomes are achieved through careful choice of surgical technique as well as strict control of medications. Although TAAD in pregnancy is associated with high mortality and morbidity to both the mother and her fetus, success in the treatment of this small subset of patients can certainly be achieved.